Analisis Potensi Pengembangan Pariwisata Inklusif Menurut Perspektif Stakeholder Di Kota Padang - Nur Maza; Alfatah Haries; Novi Yanita (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to determine the potential for inclusive tourism development in Padang City from the perspective of stakeholders. The approach used in this study is descriptive qualitative with data collection techniques through interviews, observation, and documentation. Informants in this study consisted of the Padang City Tourism Office, tourism business actors, academics, disability communities, and tourists. Data analysis was carried out using data reduction, data presentation, and conclusion drawing methods. There are five indicators used to measure tourism inclusivity, namely staff management, accessible tour operators, accessible facilities, affordable accommodation, and the availability of transportation provided by the government. The results of the study indicate that Padang City is not yet ready to support inclusive tourism because there are still various limitations in staff management that does not provide special staff for tourists with disabilities, tour operators that do not provide friendly and accessible tour packages for all groups, public facilities and accommodations do not fully meet accessibility standards, and public transportation in Padang City is not inclusive for wheelchair users or other groups with special needs.  Based on the analysis results, it is recommended that the government and stakeholders improve human resource training in the tourism sector, add supporting facilities for tourists with special needs, improve transportation infrastructure to tourist destinations, and strengthen cross-sector collaboration in designing inclusive and sustainable tourism policies in Padang City.